Desa Bebas Plastik: Inovasi Pengolahan Limbah Plastik dalam Membangun Kesadaran dan Kemandirian Masyarakat PKK Desa Ngringo untuk Lingkungan Berkelanjutan - Ambarwati, Septiana; Parida Hutapea, Henny; Wahyu Banuwati, Ameilia; Fuadah, Fani (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2026)
The increasing consumption of plastic, particularly single-use packaging, has led to a significant rise in household plastic waste, which poses a potential threat to environmental sustainability. One type of waste that remains underutilized is metallic plastic packaging. This Community Service activity aimed to enhance community knowledge and skills in processing metallic plastic packaging waste into handicraft products with functional value and economic potential. The activity was conducted in collaboration with the Family Welfare and Empowerment Group (PKK) of Ngringo Village, Karanganyar, involving 15 participants. The methods employed included a preliminary survey, educational outreach, hands-on practical training, and continuous mentoring. The effectiveness of the program was evaluated using pre-test and post-test assessments analyzed through the normalized gain (N-gain) method. The results demonstrated an improvement in participants’ knowledge and skills following the training, with an average N-gain value of 0.68, which falls within the moderate-to-high category. These findings indicate that the metallic plastic packaging waste processing training was effective in enhancing community capacity. Furthermore, the activity not only contributed to reducing plastic waste generation but also promoted the implementation of circular economy principles.